Commodifying health care: the UK's National Health Service and the Independent Sector Treatment Centre Programme. (1st October 2008) - ,; ,
Abstract : Since the year 2000 successive British governments have pushed ahead with the transformation of the National Health Service into a health care market with a strong component of for-profit provision. Focusing on the crucial first step in the privatisation of clinical services, this article examines how the four key requirements for the commodification of a public service were fulfilled —— first, breaking up health care into standardised units that could be priced; second, inducing the public to use the new commodified services; third, inducing the workforce to work for shareholders; and fourth, getting the state to underwrite the risk involved. What emerges is a story of the deep penetration of the UK state by the private health care industry, including major players with a serious history of fraud.